2016
DOI: 10.21548/28-2-1470
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Characterisation of Grape Rootstocks

Abstract: Ten grape rootstocks were characterised for their various morphological, physiological and biochemical parameters. Significant differences were observed for most of the parameters studied. Rootstocks in the group of Vitis berlandierii × Vitis rupestris, such as 110 R, 1103 P, 99 R and B2-56, had a significantly higher content of total phenols, flavon-3-ols, flaveonoids, proline and total protein. Optimum C/N ratios in the mother vines of these rootstocks helped attain better rooting percentages of hardwood cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
2
9
0
6
Order By: Relevance
“…A higher photosynthetic rate and lower transpiration rate was observed in Thompson Seedless grafted onto 110R, 1103P and 99 R rootstocks, and the least was recorded on St. George and own rooted vines (data not shown). The increased yield in these rootstocks may be attributed to increased carboxylation efficiency and increased water-use efficiency, which supports the earlier findings of Satisha et al (2008) indicating 110R and 1103 P to be drought tolerant rootstocks with high stomatal conductance and water-use efficiency under dry climatic conditions.…”
Section: Yield Parameterssupporting
confidence: 88%
“…A higher photosynthetic rate and lower transpiration rate was observed in Thompson Seedless grafted onto 110R, 1103P and 99 R rootstocks, and the least was recorded on St. George and own rooted vines (data not shown). The increased yield in these rootstocks may be attributed to increased carboxylation efficiency and increased water-use efficiency, which supports the earlier findings of Satisha et al (2008) indicating 110R and 1103 P to be drought tolerant rootstocks with high stomatal conductance and water-use efficiency under dry climatic conditions.…”
Section: Yield Parameterssupporting
confidence: 88%
“…The mechanism of this influence is not well understood but growth regulators such as auxin may be involved. Several reports documented the effect of the rootstock on the biochemical composition, in particular in terms of enzymes and phenols, of the scion of various species, such as almond (Zrig et al, 2011), grape (Satisha et al, 2007) and melon (Schmutz and Lüdders, 1999). Zrig et al (2015) emphasised the photo-protective role of anthocyanins against photo-oxidation during salinity stress in Garnem rootstock total antioxidant activity was positively correlated with carotenoids and anthocyanins concentrations more than with polyamines.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in phenol content in Dogridge was also correlated with higher root length (Somkuwar et al, 2011). Most of the biochemical constituent's viz., enzymes, plant hormones, proteins, and amino acids, as well as phenolic compounds are synthesized in the plant system with the help of various micronutrients as a co factor in their synthesis (Satisha et al, 2007). Stino et al (2011) reported that highest grafting survival percentage attained by grafting Superior Seedless on Romani Ahmar was associated with the highest indoles content, which might be the reason for this high percent due to its effect on enhancing cell division.…”
Section: Biochemical Compositionmentioning
confidence: 99%